Anti-VEGF Treatment Strategies for Wet AMD - Jaclyn L. Kovach; Stephen G. Schwartz; Harry W. Flynn; Ingrid U. Scott (Journal of Ophthalmology)
Over the past few years, antivascular endothelial growth factor (VEGF) therapy has become a standard treatment for neovascular age-related macular degeneration (AMD). During this time, treatment strategies have evolved from a monthly dosing schedule to individualized regimens. This paper will review the currently available anti-VEGF agents and evidence-based treatment strategies.